ANALISIS LEVEL SOAL ULANGAN AKHIR SEMESTER (UAS) SEMESTER GENAP TAHUN PELAJARAN 2018/2019 MATA PELAJARAN GEOGRAFI SMA/MA DI KOTA PADANG - Yesni Gusnawati; Syafri Anwar (JURUSAN GEOGRAFI FIS UNP, 2020)
ABSTRACT The research was motivated by most of high school level final examination questions in Padang City only test student low order thinking skill (LOTS) and there are teachers who are still having difficulties in making HOTS questions. The purpose of this research is to find out: 1) Cognitive level of UAS even semester for geography subjects in 2018/2019 in Padang City; 2) The obstacle of teacher in making HOTS questions; 3) The efforts made by teachers in overcoming these obstacles. This study used descriptive qualitative method. Data collection technique using documentation and interview. The results showed the matter of geography UAS in Padang City dominated by C2 of 188 questions (42,72%), C1 is 121 questions (27,5%), C3 is 67 questions (15,22%), 59 questions (13,40%) were catergorized C4, 5 questions (1,13%) with C5 category and there are no questions with C6. The obstacle of the teacher in making HOTS questions is: 1) Time making questions; 2) student are not able to answer HOTS questions; 3) The teacher less understand to make HOTS questions; 4) The unavailability of handbook for student. The efforts in overcoming these constraint are: 1) prepare questions before the lesson; 2) Creating learning that leads to HOTS; 3) MGMP forum ; 4) Provide adequate facilities. Keywords : HOTS, UAS, Cognitive aspects, Bloom’s Taxonomy